Digital Literacy and Ethical Decision-Making Among Counselors Using AI Assessment Tools - Saidah, Saidah (Yayasan Minang Darussalam, 2025)
The rapid integration of artificial intelligence (AI) into counseling practices presents both opportunities and ethical dilemmas. This study explores the relationship between digital literacy and ethical decision-making among counselors who utilize AI-based assessment tools. Using a mixed-methods approach, quantitative data were gathered through structured questionnaires, while qualitative insights were obtained via semi-structured interviews with licensed counselors in diverse educational and clinical settings. The findings indicate that counselors with higher levels of digital literacy demonstrate greater competence in navigating ethical complexities related to data privacy, informed consent, algorithmic bias, and client autonomy. Furthermore, digital literacy mediates counselors’ ability to critically evaluate the limitations of AI-generated outputs and apply professional judgment responsibly. This study underscores the need for continuous digital ethics training within counselor education programs and proposes a framework for integrating ethical AI usage into counseling standards. The results contribute to a deeper understanding of how digital competencies shape ethical practices in technology-enhanced counseling environments.